Hubungan Self-Doubt dengan Resiliensi pada Remaja: Studi pada Siswa SMA Negeri - Muhammad Maulana; Muhammad Andri Setiawan; Muhammad Arsyad (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Adolescence is a developmental period marked by academic demands, social expectations, and emotional changes that may increase vulnerability to self-doubt. Self-doubt reflects uncertainty about one’s abilities and may weaken students’ capacity to cope with challenges. Resilience, on the other hand, enables adolescents to adapt positively, recover from difficulties, and maintain psychological functioning under pressure. This study aimed to examine the relationship between self-doubt and resilience among public high school students. A quantitative correlational design was employed involving 111 students from grades 10 and 11 selected through stratified random sampling. Data were collected using a self-doubt scale based on Oleson and Steckler’s concept and a resilience scale based on Reivich and ShattÃ©’s framework, both using a five-point Likert format. Data analysis was conducted using Pearson’s product–moment correlation after the assumptions of normality and linearity were fulfilled. The results revealed a strong and significant negative relationship between self-doubt and resilience (r = âˆ’0.714, p < 0.001). This finding indicates that students with higher levels of self-doubt tend to demonstrate lower levels of resilience. Descriptive results also showed that most students were in the low to moderate category of self-doubt, while their resilience tended to be in the moderate category. These findings suggest that self-doubt is an important psychological factor associated with adolescents’ resilience. The study provides practical implications for school guidance and counseling services, particularly in designing preventive and developmental programs that help students reduce self-doubt, strengthen self-confidence, enhance adaptive coping, and build resilience through support from teachers, counselors, peers, and families.